2011
DOI: 10.1021/ef101327d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Middle Distillate Yields during Crude Oil Hydrotreatment in a Trickle-Bed Reactor

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…It can be observed that the presence of hydrogen improved the naphtha fraction more compared to the cyclohexane donor solvent. A similar improvement in naphtha and middle distillate fractions was observed by Jarullah et al [30], after hydrotreatment of a whole crude oil in a trickle-bed reactor. This observation is also consistent with the results reported on API gravity and viscosity of the feed and upgraded oils (see Table 7).…”
Section: True Boiling Point (Tbp) Distributionsupporting
confidence: 82%
“…It can be observed that the presence of hydrogen improved the naphtha fraction more compared to the cyclohexane donor solvent. A similar improvement in naphtha and middle distillate fractions was observed by Jarullah et al [30], after hydrotreatment of a whole crude oil in a trickle-bed reactor. This observation is also consistent with the results reported on API gravity and viscosity of the feed and upgraded oils (see Table 7).…”
Section: True Boiling Point (Tbp) Distributionsupporting
confidence: 82%
“…In summary, the upgraded oil with hydrogen contained more low-boiling hydrocarbon components, followed by the upgraded oil obtained when nitrogen gas was used relative to the THAI oil studied. Jarullah and co-workers [41] reported hydrotreatment of conventional crude oil in a trickle-bed reactor, from which they deduced that the yield of middle distillate fractions increased thereafter. This can be attributed to hydrocracking, hydrogenation of free radicals, aromatics and olefins, and the removal of heteroatoms.…”
Section: Upgraded Oils True Boiling Point (Tbp) Distributionmentioning
confidence: 99%
“…In refineries, crude oil is distilled to various fractions, in which the main distillate fractions including light naphtha, heavy naphtha, kerosene and gas oil are very valuable (Jarullah et al 2011;Prins 2001;Qian et al 2013). There are serious regulations, especially in Europe and USA, which limit the impurities in the main petroleum fractions.…”
Section: Introductionmentioning
confidence: 99%